Global service learning: A unique educational pathway for community engagement and student scholarship development. Issue 2 (15th February 2021) - Miller, Monica L.; Schellhase, Ellen; Whicker, Hadley; Manji, Imran; Karwa, Rakhi; Pastakia, Sonak D.; Kimani, Samwel
Abstract: Introduction: Service learning is an educational tool that can augment classroom learning with experiential practice. The Purdue Kenya Partnership (PKP) has utilized elective service learning activities to aid student development in research, community engagement, and professional writing. Objective: The purpose of this research is to share PKP's experience in strategically engaging student pharmacists in service learning while completing an 8‐week global health advanced pharmacy practice experience in Eldoret, Kenya. Methods: A retrospective review of PKP's service learning activities conducted between 2004 and 2019 was completed. An outcome‐approach logic model was used to evaluate the program using descriptive statistics to capture the scholarly output and impacts. Results: PKP has established sustainable relationships with five community partners and completed 23 unique service learning projects lead by 69 individual students. A total of $76 510 was awarded for service learning projects between 2008 and 2019. Students translated their service learning activities into 64 professional posters at regional, national, and international meetings as well as 12 manuscripts between 2004 and 2019. Conclusion: PKP has impacted student development through their inclusion of service learning activities. It is used as a pathway for research skill development as evidenced by the student posters, grants, and publications as well as developed long‐standing community partner relationships.